Variação na forma craniana em morcegos neotropicais (Chiroptera: Yangochiroptera) - Hoppe, João Paulo Maires (2016)
Bats are among the most prevalent components of the mammalian fauna, represented by more than 400 species in the Neotropical Region. The group has an unmatched diversity in feeding habits, without peer in any other vertebrate taxon, especially in the leaf-nosed bats of the family Phyllostomidae. This variety is reflected on the main physical structure for interaction with the environment, the skull. Skull shape variation can be due to ecological, evolutionary, and allometric factors, as well as their interactions, and must be analyzed together in order to avoid confusion between the variables. Here, I apply Geometric Morphometric tools to analyze shape change variation in the evolution of bats, using 146 species representing all nine families occurring in the Neotropical Region. Contrary to other mammalian groups, allometry has almost negligible effects in these bats, explaining approximately 6% of the skull shape variation in pure allometric models. On the other hand, feeding guilds explain nearly 30% of the skull shape variation, while the taxonomic subfamily level has nearly 40%. The same patterns occur when allometric effects are nested within these categories in a Nested ANOVA. Adding phylogenetic information in the models resulted similar correlations of models without it, but remarkably different values of significance, the majority no longer significant. I found small, albeit significant, phylogenetic signal for the majority of the analyzed groups, showing that phylogenetic close species are more similar than expected by random, but with significant convergent evolution, exemplified by the nectarivores (Lonchophyllinae and Glossophaginae), some frugivores (Carollinae and Rhinophyllinae), and the gleaning omnivores (Macrotinae, Micronycterinae, Lonchorhininae, Phyllostominae and Glyphonycterinae). The results imply that skull shape variation comes from intrinsic properties of each evolutionary lineage, and not by allometric tendencies.